Training in data collection using spatial sampling approach: Training description and evaluation - Faculty Geo-Information Science and Earth Observation-University of Twente (ITC-UoT) (Universidade Eduardo Mondlane, 2024)
Three main activities, completely focused on the data collection, were conducted: a) Internal preparation: On Monday November 13th the project partners responsible for the training revisited the training schedule and content. It was adjusted due to a sickness of one of the instructors. b) The training workshop on the fieldwork data collection workflow and mobile app: Instructors presented the suggested workflow for data collection, the mobile app interface, and its functionalities. The components of the apps and the background data were explained in detail. The mobile app functionality was first demonstrated using screen cast (AirDroid cast). After that, participants tried themselves and tested all the necessary functions to perform the data collection on the field. Participants were also able to provide feedback on the mobile app which was incorporated in a new version. Reference data such as villages, sub-districts and roads were also added. Finally, participants collected mock data on the field (an area that mimics conditions similar to those they might encounter in reality). The collected data was discussed to highlight some issues, for example, how pictures were taken, and how this could be improved. c) Logistics: On Friday 17th after a wrapping-up session, the local team organized participants in groups and assigned their tasks (where to collect data). The training was originally planned to be given in English. However, in consultation with the local team and participants, it was decided to be delivered in Spanish. Translation (from/to) Portuguese was available as needed.